Bacteriuria Profile and Associated Risk Factors among Pregnant Women with and Without Diabetes at Al-Jala Hospital (Tripoli - Libya) - Al-Griw, Huda; Marwan Draid; Amer Elgerwi (Khalij-Libya Journal of Dental and Medical Research, 2024)
Background and objectives: This study was conducted to identify the pathogenic bacteriuria profile and associated risk factors in pregnant women with and without diabetes. Methods: Six hundred urine samples were examined from pregnant women in different age groups: 100 non-diabetics with asymptomatic bacteriuria (ABU), 100 non-diabetics with symptomatic bacteriuria (SBU), 200 diabetics with (ABU) and 200 diabetics with SBU. The culture media were prepared according to the manufacturer’s instructions. Results: The number of positive cultures among asymptomatic UTI-tested women was 106 out of 300 (20%), that 60/200 cases (30%) in diabetic patients and 46/100 cases (46%) in non-diabetic patients. The number of positive cultures among symptomatic UTI-tested women was 195 of 300 (65%), 100/200 cases (50%) in diabetic patients and 95/ 100 (95%) in non-diabetic patients, with a higher percentage isolated from E. coli isolated from both non-diabetic pregnant women at the rate of (26.1%) and diabetic pregnant women at the rate of (56.7%) with asymptomatic bacteriuria as well as a higher percentage isolated at the rate of (30%) from non-diabetic pregnant women and at the rate of (34.7%) from diabetic pregnant women with symptomatic bacteriuria. Escherichia coli is the most important cause of UTIs, particularly in pregnant women with diabetes. Conclusion: This study has highlighted the need for greater awareness of urinary tract infection and the expansion of prevention and treatment services for pregnant women. Therefore, it is suggested that routine screening of patients and antimicrobial therapy should be guided by both in vitro susceptibility and clinical response. المقدمة والهدف: تم إجراء هذه الدراسة لتحديد انواع بكتيريا البول الممرضة والعوامل المرتبطة بها في النساء الحوامل المصابات وغير مصابات بداء السكري. طرق الدراسة: تم فحص 600 عينة من البول من نساء حوامل في فئات عمرية مختلفة: 100 من النساء اللواتي لا يعانين من داء السكري ولا تظهر عليهم اعراض التهاب المسالك البولية و 100 لايعانون من اعراض السكري وتظهر عليهم اعراض التهاب المسالك البولية، 200 من النساء اللواتي يعانين من داء السكري ولا تظهر عليهم اعراض التهاب المسالك البولية ، و 200 من النساء اللواتي يعانين من داء السكري و تظهر عليهم اعراض التهاب المسالك البولية. تم تحضير وسائط الزرع وفقًا لتعليمات الشركة المصنعة. النتائج: اظهرت النتائج بان عدد المزارع الايجابية في النساء الحوامل اللواتي ليس لديهم اعراض التهاب المسالك البولية هو 106 \300 (20%)، منهم 60 حالة من عدد 200 من هن مصابات بمرض السكري، و 46 حالة من عدد 100 (46%) ممن هن غير مصابات بمرض السكري. كما كانت نتائج المزارع البكتيرية الايجابية من النساء الحوامل وتظهر عليهن اعراض المسالك البولية هو 195 من بين 300 (65%)، منهم 100حالة موجبة من عدد 200 أي (50%) ممن يعانون من مرض السكري و عدد 95 حالة موجبة من عدد 100 أي (95%) ممن لا يعانون من مرض السكري مع وجود نسبة عالية من عزلات الاشريكية القولونية في النساء الحوامل الذي لاتظهر عليهم اعراض بكتريا البول سواء المرضي بالسكري وبنسبة (56.7%)او الغير مرضى بالسكري وبالنسبة (26.1%). وكذلك نسبة عالية من هذه البكتريا في النساء التي تظهر عليهم اعراض المسالك ولذيهم السكري وبنسبة (34.7%) وممن ليس لديهم السكري وبنسبة (30%). الاستنتاج: نستنتج من هذه الدراسة ان الإشريكية القولونية من أهم أسباب الإصابة بالتهابات المسالك البولية، خاصة عند النساء الحوامل المصابات بداء السكري. وفي الخلاصة، فقد أبرزت هذه الدراسة الحاجة إلى زيادة الوعي بالتهاب المسالك البولية وتوسيع خدمات الوقاية والعلاج للنساء الحوامل. لذلك يُقترح إجراء فحص دوري للمرضى والعلاج بالمضاد للميكروبات بنأء على اختبار الحساسية في المختبر والاستجابة السريرية